Determination of the water content of an ex vivo porcine liver - Busch Christoph; Rupitsch Stefan J.; Moeller Knut (Current Directions in Biomedical Engineering, 2023)
When modeling High-Frequency (HF) surgical applications the choice of the right dielectric tissue parameters is a key factor for success. The water content of biological tissue is of particular importance since the dielectric tissue properties highly depend on it. Therefore, we investigate a simple and fast method for the determination of relative tissue water content using small samples of an ex vivo porcine liver. To identify the water content, we utilized a desiccation and weighing experiment. It is assumed that the weight loss can be directly attributed to the loss of water in the case of desiccation. Based on the ratio between the initial and dry weight of a sample, the relative water content can be determined. The drying procedure lasted 28 hours, with 16 small samples taken from an ex vivo porcine liver. At the end of the drying procedure, a relative tissue water content of 69.6 % ± 1.1 % was observed. Using a curve fit to the measured data, it can be assumed that approximately 99.3 % of the tissue water content had evaporated by the end of the drying process. With the drying and weighing method used, we were able to determine the water content of the ex vivo porcine liver relatively easily. However, our results also suggest that optimizations of the applied method should be considered for future measurements. Especially, if a faster determination of the water content is required, which in a broader sense should afterward serve for the validation of a simulation model.